Estimation and Application for Line Impedance Between IBR and POM - Woo-Hyun Kim; Ye-Chan Kim; Seung-Ho Song (Energies, 2025)
With the increasing integration of Inverter-Based Resources (IBRs) into power grids, accurate estimation of line impedance between the Point of Connection (POC) and the Point of Measurement (POM) has become critical to ensure stable and efficient reactive power control. However, conventional impedance estimation methods often face challenges such as power quality degradation and sensitivity to voltage unbalance. This paper presents a method to improve the reactive power control performance of Inverter-Based Resources (IBRs) by estimating the line impedance between the Point of Connection (POC) and the Point of Measurement (POM) and utilize the estimated impedance into control. The impact of voltage drop caused by line impedance on reactive power delivery is analyzed, and a compensation method is designed to mitigate the resulting control errors. The line impedance is estimated through a negative-sequence current injection technique, under the condition that the voltage phases at the two measurement points are synchronized. To address potential voltage unbalance issues that may arise during the injection process, a dedicated compensation algorithm is also proposed. The proposed algorithm is validated through both simulations and lab-scale experiments, demonstrating that the line impedance can be estimated with an error of less than 2%, while effectively compensating for reactive power distortion at the POM.